¿La ciudad puede llegar a ser educadora? - Pérez, Patricia (2005)
This article analyses the bonds between city and education. It sees and understands the educative spaces and processes with the notion of “educator-city” (“ciudad-educadora”). From that standpoint, it tracks the educative processes that are part of the daily experience of some immersed communities in the urban space of Porto Alegre, Brazil.